2010
DOI: 10.1007/s11199-010-9829-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-Objectification, Self-Esteem, and Gender: Testing a Moderated Mediation Model

Abstract: The purpose of the present research was to test the mediating roles of body shame and appearance anxiety in the relation between self-surveillance and self-esteem; and to investigate whether gender (male, female) and stereotypical gender roles (masculinity, femininity) moderated the proposed mediation model. Canadian undergraduate university men and women (n= 198) completed measures of self-surveillance, gender, gender roles, body shame, appearance anxiety, and selfesteem. Regression analyses demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 57 publications
(119 reference statements)
3
62
0
1
Order By: Relevance
“…The following is a list (not exhaustive) of other consequences empirically associated with self-objectification: lower intrinsic motivation and self-efficacy (Gapinski, Brownell, & LaFrance, 2003); lower self-esteem (Choma et al, 2010); less life satisfaction (Mercurio & Landry, 2008); diminished cognitive performance Gay & Castano, 2010;Quinn, Kallen, Twenge, & Fredrickson, 2006); diminished physical performance (Fredrickson & Harrison, 2005); more negative attitudes toward breastfeeding (JohnstonRobeldo, Fricker, & Pasek, 2007) and reproductive functioning (Johnston-Robledo, Sheffield, Voigt, & Wilcox-Constantine, 2007;Roberts, 2004); greater fear and perceived risk of rape (Fairchild & Rudman, 2007); greater hostility toward other women (Loya, Cowan, & Walters, 2006); more self-injury (Muehlenkamp, Swanson, & Brausch, 2005); more substance abuse (Carr & Szymanski, 2011;Harell, Fredrickson, Pomerleau, & Nolen-Hoeksema, 2006); decreased use of sexual protection (Impett, Schooler, & Tolman, 2006); more dysfunctional exercise (Strelan, Mehaffey, & Tiggemann, 2003); and more support for cosmetic surgery (Calogero, Pina, Park, & Rahemtulla, 2010;Calogero, Pina, & Sutton, 2013).…”
Section: Consequences Of Self-objectificationmentioning
confidence: 99%
“…The following is a list (not exhaustive) of other consequences empirically associated with self-objectification: lower intrinsic motivation and self-efficacy (Gapinski, Brownell, & LaFrance, 2003); lower self-esteem (Choma et al, 2010); less life satisfaction (Mercurio & Landry, 2008); diminished cognitive performance Gay & Castano, 2010;Quinn, Kallen, Twenge, & Fredrickson, 2006); diminished physical performance (Fredrickson & Harrison, 2005); more negative attitudes toward breastfeeding (JohnstonRobeldo, Fricker, & Pasek, 2007) and reproductive functioning (Johnston-Robledo, Sheffield, Voigt, & Wilcox-Constantine, 2007;Roberts, 2004); greater fear and perceived risk of rape (Fairchild & Rudman, 2007); greater hostility toward other women (Loya, Cowan, & Walters, 2006); more self-injury (Muehlenkamp, Swanson, & Brausch, 2005); more substance abuse (Carr & Szymanski, 2011;Harell, Fredrickson, Pomerleau, & Nolen-Hoeksema, 2006); decreased use of sexual protection (Impett, Schooler, & Tolman, 2006); more dysfunctional exercise (Strelan, Mehaffey, & Tiggemann, 2003); and more support for cosmetic surgery (Calogero, Pina, Park, & Rahemtulla, 2010;Calogero, Pina, & Sutton, 2013).…”
Section: Consequences Of Self-objectificationmentioning
confidence: 99%
“…In a related study, Smolak and Stein (2010) found that boys' investment in male physical attributes (e.g., strength) predicted investment in media images of men who have the muscular and lean body ideal seven months later. Researchers (e.g., Choma et al, 2010;Grogan 2010;Pompper, 2010) have suggested that the media's focus on male physical appearance may lead boys and men to feel valued for how they look more so than for who they are or what they can do, leading to a sense of objectification (Strelan & Hargreaves, 2005).…”
Section: Sociocultural Weight Pressuresmentioning
confidence: 99%
“…Researchers are curious as to what extent observing the objectified male body and experiencing pressure to achieve this ideal are related to the well-being of boys and men, especially their body dissatisfaction and body change behaviors. Several articles in this issue advance the understanding of these associations (Boroughs et al 2010;Choma et al 2010;Karazsia and Crowther 2010;Mellor et al 2010;Petrie et al 2010;Pompper 2010;Smolak and Stein 2010).…”
Section: Highlights Of Part Ii: Recognizing Individual Differences Inmentioning
confidence: 99%
“…For women in western cultures, the ideal body shape/size is very thin with large breasts (e.g., Levine and Harrison 2004), and for men the ideal is muscularity definition coupled with low body fat (Grogan and Richards 2002;Leit et al 2002;Ridgeway and Tylka 2005;Thompson and Cafri 2007). Several articles in this special issue consider how culturally-defined gender roles, as well as individuals' gender role investment and intensification, shape males and females' body image (i.e., Choma et al 2010;Pompper 2010;Smolak and Stein 2010).…”
Section: Highlights Of Part Ii: Recognizing Individual Differences Inmentioning
confidence: 99%
See 1 more Smart Citation